Membangun Pemberdayaan Masyarakat yang Berkembang dan Maju Melalui Pelatihan Pembukuan Keuangan UMKM di Desa Srimukti - Elia Rossa; Imas Mutikartini Putri; Nanditya Andini; Sindy Septiani; Eva Yanis Lafione; Aisyah Sekar Ningrum; Arinda Dwi Cahyani; Azhar Huwaiza Fathoni; Jihan Salsabilah (Institut Teknologi dan Bisnis Semarang, 2024)
Srimukti Village has great potential in the development of Micro, Small, and Medium Enterprises (MSMEs). This can be seen from the fact that most of the areas of Srimukti Village are rice fields that are used as a source of income. However, based on the results of observations and data obtained, there are still many MSME actors in Srimukti Village who do not have adequate knowledge and skills in managing their business finances. This study describes the implementation of the Community Service Program (KKN) with the theme